2017
DOI: 10.1159/000478856
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Inherited Epidermolysis Bullosa in Resource-Limited Settings: Immunohistochemistry Revisited

Abstract: Background: Immunofluorescence (IFM) antigen mapping is the most commonly used technique to diagnose and differentiate epidermolysis bullosa (EB). In India, IFM is limited to few research laboratories and is not readily available, making the diagnosis largely clinical and often inaccurate. Ob jective of the Study: To examine the diagnostic usefulness of immunohistochemistry (IHC) as compared to IFM in resource-limited settings. Methods: Forty-four consecutive EB patients were included in this study. IHC and IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The sensitivity and specificity of IFM have been compared with those of TEM or evaluated in relation to clinical diagnosis in a few case series of patients with all types of suspected EB . In only two of these studies the internal reference standard was genetic diagnosis .…”
Section: Laboratory Diagnosis Of Epidermolysis Bullosamentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity and specificity of IFM have been compared with those of TEM or evaluated in relation to clinical diagnosis in a few case series of patients with all types of suspected EB . In only two of these studies the internal reference standard was genetic diagnosis .…”
Section: Laboratory Diagnosis Of Epidermolysis Bullosamentioning
confidence: 99%
“…IFM, also called antigen mapping, on frozen sections is a rapid technique for EB subtype diagnosis that is also feasible in resource-limited settings. 62 Variations of this technique include using different panels of antibodies or different IHC detection methods. [62][63][64][65] IHC on frozen sections is possible, 62 but it requires nearly the same equipment as IFM, excluding the need for a fluorescence microscope.…”
Section: Immunofluorescence Mapping (Level Of Evidence 2+ Grade Of Recommendation C)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, in their study, Tampoia et al have suggested that the IL-6/IL-10 ratio can be used as a prognostic and predictive marker of the severity of IEB and it has been reported that this ratio is statistically higher in recessive DEB than in EBS and healthy subjects (8). Apart from immunofluorescence antigen mapping, immunohistochemistry staining could be used as a diagnostic method especially in resource-limited settings (9). Histopatho-…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest classification of EB, four clinical types have been defined, i.e., (a) EB simplex (EBS), (b) junctional EB (JEB), (c) dystrophic EB (DEB), and (d) Kindler syndrome ( 2 ). Clinical diagnosis is based on immunohistochemistry including skin biopsies and, electron microscopy to understand the histopathology of each EB prototype ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%